2004
DOI: 10.2298/mpns0404116m
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of adolescents

Abstract: Sexual life of adolescents begins at the age of 16, on average, and only every third always uses contraceptive protection, which points to a need for better education on reproductive health by using contemporary methods. It is also necessary to increase availability of contraceptives (condoms) at all places where adolescents spend time (in schools, bars, cinemas, disco clubs etc.) in order to achieve responsible sexual behavior and protection of reproductive health among youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…According to the results of the research by Kapamadžija et al, 84.3% of young high school male students had their first full sexual intercourse at the age of 18, while the average age when they had their first experience was 15.55 [12]. According to the results of Mijatović-Jovanović et al, the average age of starting sexual relations in Novi Sad was 15.6 for boys and 16.5 for girls [13]. Results of the research by Van de Bongart et al have suggested that sexual activity is closely connected to sexual behavior of the peers, which can be an explanation for early start of sexual activity of street children [14].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the research by Kapamadžija et al, 84.3% of young high school male students had their first full sexual intercourse at the age of 18, while the average age when they had their first experience was 15.55 [12]. According to the results of Mijatović-Jovanović et al, the average age of starting sexual relations in Novi Sad was 15.6 for boys and 16.5 for girls [13]. Results of the research by Van de Bongart et al have suggested that sexual activity is closely connected to sexual behavior of the peers, which can be an explanation for early start of sexual activity of street children [14].…”
Section: Resultsmentioning
confidence: 99%
“…Nesklad između biološke i psihosocijalne zrelosti stvara mogućnost za visokorizična ponašanja koja mogu da naruše psihofizičko zdravlje mlade osobe [5].…”
Section: Uvodunclassified
“…In Serbia, research shows that young people are at risk and that they are engaging in sexual relations earlier without the correct information about sexual and reproductive health ( 2 , 3 , 4 ). One particular concern is the fact that 3.4% of girls had had unwanted sexual intercourse ( 5 ) and every seventh girl had experienced some form of abuse within a relationship by the end of adolescence ( 6 ).…”
Section: Introductionmentioning
confidence: 99%